Estudo teórico da Tetraazaporfirina de Rutênio e seus derivados para o transporte do monóxido nítrico - (:unkn) unknown (Universidade Estadual de Goiás, 2009)
The ruthenium tetraazaporphyrin (RuTAP) complexes are aromatic compounds derived from porphyrins with 18 π electrons. These compounds have low toxicity, high chemical and thermal stability, and in turn they are strong candidates for technological and pharmacological applications such as nitrogen monoxide carrier in living organisms. In order to investigate the possibility to use the RuTAP complexes as nitrogen monoxide carrier, calculations of energetic, geometric and electronic parameters using molecular quantum chemistry methods were carried out for NO attached to RuTAP without axial ligand and with axial ligand (Fluorine, Chlorine, ammonia, and pyridine) for the oxidation state varying from +1 to +7. The calculation results show that the ON−TAP bonding is strongly influenced by the oxidation state and is stronger for RuTAP without ligand when compared to RuTAP with axial ligand for the same oxidation state. The shorter bond length is calculated for oxidation state +3 for all complexes, except for the fluorine ligand in which the shortest bond length is obtained for oxidation state +1. The calculations also show that the interaction of the NO group with RuTAP is strongly influenced by the nature of the ligand. Based on the result of this dissertation, we can suggest the use of RuTAP in the modeling of NO carrier.
Keywords: Tetraazaporfirina de rutênio; Monóxido de nitrogênio; Ruthenium tetraazaporphyrin; Nitrogen monoxide; NO carrier; Porphyrazines; B3LYP; CIENCIAS EXATAS E DA TERRA::QUIMICA